Advanced multifunctional wound dressing hydrogels as drug carriers - Farokhi, Mehdi (2022)
Skin injuries, especially chronic wounds, remain a significant healthcare system problem. The number of burns, diabetic patients, pressure ulcers, and other damages is also growing, particularly in elderly populations. Several investigations are pursued in designing more effective therapeutics for treating different wound injuries. These efforts have resulted in developing multifunctional wound dressings to improve wound repair. For this, preparing multifunctional dressings using various methods has provided a new attitude to support effective skin regeneration. This review focuses on the recent developments in designing multifunctional hydrogel dressings with hemostasis, adhesiveness, antibacterial, and antioxidant properties.